Drucker on marketing : lessons from the world's most influential business thinker - Cohen, William A., 1937- (McGraw-Hill, 2013)
Providing unique insight into the mind of one of the 20th century's greatest thinkers; this book presents Drucker's most salient ideas on marketing in a framework that not only outlines his marketing philosophy; but provides practical advice on how to achieve marketing goals in today's business setting. --